Estudio comparativo sobre la satisfacción laboral entre empleados de planilla y empleados de intermediación laboral (in-plants) en dos empresas farmacéuticas multinacionales en Perú - Alvites Paz Soldán, Fiorella Alejandra (2021)
Currently, companies face various challenges of globalization, such as optimizing their processes, improving productivity, better time and work management, among others, so that their benefits are increasing. That is why companies seek innovative solutions in the market that allow them to achieve these objectives. This leads to considering different hiring modalities, cross functional work styles and a low hierarchy that allows more horizontal communication. In line with this, one of the contracting modalities that has become more relevant in recent times is labor intermediation, which allows companies to concentrate efforts on their core business, by hiring, through a third-party company, internal personnel. -plant that is dedicated to temporary, complementary or specialized services. Although this modality brings many benefits, such as increased productivity and better response capacity to meet customer needs, it also represents challenges in terms of personnel management and satisfaction. Thus, the objective of this study is to compare the job satisfaction of payroll personnel and personnel hired through labor intermediation (in-plants) in two multinational pharmaceutical companies established in Peru. To carry out this study, a survey known as the Job Descriptive Index (JDI) will be used. This index will allow a descriptive evaluation of the job satisfaction of both groups through five dimensions: "Current job", “Current salary”, “Promotion opportunities”, “Supervision” and “Co-workers”. To do this, the evaluation results of the characteristics of each of the five dimensions for both groups (payroll workers and inplants) will be compared. As a result of the general hypothesis, no differences were found in the study subject groups, since it is concluded that both are equal in the proportion of their assessment with respect to the observed characteristics of job satisfaction.